Strategic planning of the activities of mobile units as an element of sustainable mobility - Oleynik Pavel; Kazaryan Ruben; Doroshin Ivan; Kisel Vadim (BIO Web of Conferences)
Nowadays, active development of the territory of the Far North, Siberia and the Far East is being carried out, as a rule, by the forces of mobile construction organizations and their units. We are talking about increasing the sustainable mobility of construction organizations. They perform a huge range of work, including pioneer development of territories and the construction of various concentrated and dispersed construction projects. At the same time, the activities of mobile units differ significantly from the activities of traditional construction organizations, first of all, in that they have to autonomously solve the entire aspect of life support tasks far from the places of their permanent deployment. In this context, ensuring the dependable provision of efficient production resources to mobile units becomes crucial. These resources enable swift transformation of materials, structures, and equipment into finished construction products, minimizing human labor costs at the construction site. The paper presents an approach to choosing a strategy for the activities of mobile units using the example of pioneer development of a territory. The optimal planning model is described in detail, and methods for obtaining an integer solution are indicated.